PENINGKATAN HASIL BELAJAR SISWA PADA PEMBELAJARAN PKn MELALUI PENGGUNAAN PENDEKATAN PERKEMBANGAN MORAL KOGNITIF DENGAN DISKUSI DILEMA MORAL - Ariani, Susi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This study originated from the reality in which learning Civics still using expository approach, teachers focus on the business of planting various kinds of goodness through examples,advice, warnings, and less emphasis on the development of reasoning. To overcome the action with the use of cognitive moral development approach to the discussion of moral dilemmas. That research use approach qualitative and quantitative, while this type is Research Action Class (PTK) with device research cover, (1)Planning, (2)Execution, (3) Perception/observation, and (4) Refleksi. Result of research be grow up result of RPP, execution, and result learn student. Become can be concluded that study PKn by using cognitive moral development approach to the discussion of moral dilemmas can improve result learn IV class student 18 Tarok Dipo Bukittinggi. Kata Kunci: hasil belajar; pembelajaran PKn; pendekatan perkembangan moral kognitif dengan diskusi dilema moral